Mnemotechniczne teksty staropolskie ze zbiorów gnieźnieńskich - Łukaszewski, Jakub; Wydra, Wiesław (Slavia Occidentalis, 2022)
The article contains an edition of mnemonic poems from the late 15th century and from the first half of the 16th century, discovered in the Archdiocese Archives in Gniezno. They contain the conditions for good confession, the church commandments, and reminders of the Franciscan rule.